Transformasi Surat Berharga Konvensional ke Surat Berharga Digital dalam Perspektif Hukum Indonesia (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of digital technology has significantly transformed financial transaction systems, including the use of securities. Conventional securities, which traditionally function as instruments of payment, evidence, and transfer of rights, face various challenges such as document forgery, loss, and administrative inefficiency. These conditions have encouraged the digitalization of securities, requiring adjustments within the Indonesian legal framework. This study aims to analyze the transformation of securities from conventional forms to digital formats within the perspective of Indonesian law and to assess the adequacy of existing regulations in addressing such developments. The research employs a normative juridical approach by examining primary legal materials in the form of statutory regulations and secondary legal materials consisting of legal literature and previous studies. The findings indicate that although electronic documents have been legally recognized as valid evidence, there is no specific and comprehensive regulation governing digital securities. Consequently, legal uncertainty remains regarding the transfer of rights, evidentiary strength, and legal protection for holders of digital securities. This study is expected to contribute conceptually to the development of adaptive legal regulations that ensure legal certainty and protection in the context of modern digital transactions.